Transcriptomic Analysis Reveals a Sex-Dimorphic Influence of GAT-2 on Murine Liver Function - Fu, Jian; Zhang, Qingzhuo; Wu, Zebiao; Hong, Changming; Zhu, Congrui (Frontiers in Nutrition, 2021)
Accumulating evidence shows that the γ-amino butyric acid (GABA)ergic system affects the functions of different organs, and liver is one of the most sex-dimorphic organs in animals. However, whether and how the GABAergic system influences liver function in a sex-specific manner at the intrinsic molecular level remains elusive. In this study, firstly, we find that the levels of GABA are significantly increased in the livers of female mice with GABA transporter (GAT)-2 deficiency (KO) whereas it only slightly increased in male GAT-2 KO mice. Apart from the amino acid profiles, the expressions of toll-like receptors (TLRs) also differ in the livers of female and male KO mice. Moreover, RNA-seq results show 2,227 differentially expressed genes (DEGs) in which 1,030 are upregulated whereas 1,197 that are downregulated in the livers of female KO mice. Notably, oxidative phosphorylation, non-alcoholic fatty liver disease, Huntington's disease, and peroxisome proliferator-activated receptor (PPAR) signaling pathways are highly enriched by GAT-2 deficiency, indicating that these pathways probably meditate the effects of GAT-2 on female liver functions, on the other hand, only 1,233 DEGs, including 474 are upregulated and 759 are downregulated in the livers of male KO mice. Interestingly, retinol metabolism, PPAR signaling pathway, and tuberculosis pathways are substantially enriched by GAT-2 deficiency, suggesting that these pathways may be responsible for the effects of GAT-2 on male liver functions. Collectively, our results reveal the sex-dimorphic effects of GAT-2 in guiding liver functions, and we propose that targeting the GABAergic system (e.g., GATs) in a sex-specific manner could provide previously unidentified therapeutic opportunities for liver diseases.